Technological Change and its Impact on the Labor Market in Egypt - Mona Farid Badran (International Telecommunications Society (ITS), 2019)
The current study aims at analyzing the impact of technological change and innovations on the labor market in Egypt. Using the panel data of Egyptian Labor Market Panel Survey (ELMPS) 1998, 2006, and 2012 as well as the initial year of ELMPS 1988, a quadratic form of equation for employment is estimated and two approaches were applied. The first one is collaborated by applying the Ordinary Least Square (OLS) estimation method and taking the difference between the rounds of the ELMPS database; three regressions were estimated for the following, namely total labor force (males and females), a regression for male workers as well as another regression for female workers on wage and wage squared. The second approach is estimated by applying the panel model techniques using the Fixed Effects Model as well as the Random Effects Model to analyze the impact of technological change on the Egyptian labor market. Results of the study reveal that the impact of technological change on employment is evident in the years 2006 and 2012 causing job polarization in the Egyptian labor market as revealed in the first approach. Moreover, the findings show that in the second approach there exists a J-shaped relationship between employment growth and wage and wage squared as control variables. The present study provides an overview of the related literature; moreover, it addresses and analyzes the impact technological change has on the labor market. Finally, the paper provides policy recommendations for forward-looking labor market policies in Egypt.
Keywords: J21; J24; L96; 330; technological change; labor market; skills; digital economy; MENA; Fixed Effects Model; Random Effects Model; 3rd Industrial Revolution; 4th Industrial Revolution; Egypt